1982
DOI: 10.1530/acta.0.0990239
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complexes in diabetics with severe microangiopathy: evaluation by two different methods

Abstract: Abstract. An investigation on circulating immune complexes (AgAb) was carried out in 80 diabetics with severe microangiopathy and in 71 diabetics without microvascular lesions. The duration of the disease, the type of diabetes, the type of treatment and the main localization of microangiopathy (retinopathy and nephropathy) were taken into account. AgAb were detected by two different methods: the solid phase Clq binding test (ClqSP) and the conglutinin binding test (KgBt). AgAb detected by ClqSP were increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…This relationship between vascular complications and levels of CIC in the sera of diabetic patients has also been reported by others (Adreani et al, 1982;Di Mario et al, 1983;Baranao et al, 1985;Baydanoff et al, 1988;Turk et al, 2001). Thus, while some studies reported a correlation between vascular complications and the detection of elastinspecific CIC (Baydanoff et al, 1988), others have reported AGE-containing CIC (Turk et al, 2001), insulin-CIC (Triolo et al, 1984), and/or total CIC (Adreani et al, 1982;Di Mario et al, 1983;Baranao et al, 1985).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This relationship between vascular complications and levels of CIC in the sera of diabetic patients has also been reported by others (Adreani et al, 1982;Di Mario et al, 1983;Baranao et al, 1985;Baydanoff et al, 1988;Turk et al, 2001). Thus, while some studies reported a correlation between vascular complications and the detection of elastinspecific CIC (Baydanoff et al, 1988), others have reported AGE-containing CIC (Turk et al, 2001), insulin-CIC (Triolo et al, 1984), and/or total CIC (Adreani et al, 1982;Di Mario et al, 1983;Baranao et al, 1985).…”
Section: Discussionsupporting
confidence: 87%
“…CIC, detected by RIA, were higher in long standing Type1 diabetics. These differences in the results can be explained by the view that CIC present in diabetics seems are heterogeneous in nature with a proportion of them being related to the occurrence of microangiopathy (Adreani et al, 1982). Thus, as reported herein, diabetics with microangiopathy showed increased levels of CIC as compared to controls.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…15 The determination of immune complexes and the characteristics and criteria used to establish positive limits of the technique have been described elsewhere. 8 Metabolic control was evaluated by assay of glycosylated hemoglobin (HbAj) with column chromatography using the Bio Rad kit (Bio-Rad, Richmond, California). The upper limit of normal values in our laboratory was 9%, intraassay variation was 0.3% (HbA, < 7%) and 0.6% (HbA, > 7%), and interassay variation was 0.8% and 1.4%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…6 ' 7 The benefits of purified insulin on late diabetic complications, particularly those of a microangiopathic nature, are not yet known. Marked prevalence of circulating immune complexes in diabetic subjects with severe microangiopathy 8 suggests, however, that immune factors may play a role in the pathogenesis and/or in the evolution of microangiopathy.…”
mentioning
confidence: 99%